From the protest movement to the party in power. Green development in Germany - Brzozowski-Zabost, Grzegorz (Studia Ecologiae et Bioethicae, 2008)
The author presents in this paper the developing process of German Green Party. In the 1970s new social movements like environmentalists, peace organizations and feminist founded political party The Greens (Die Grünen). It was an act of opposition against pollution, use of nuclear power, and some aspects of life in highly developed and industrialized society, the formal inauguration was held 1980 in West Germany. 1990 three civil rights groups in East Germany combined to form Bündnis 90, which merged with Die Grünen after long uniting process in 1993. 18 years after foundation they built together with social democrats from SPD government which lasted for two term of office between 1998 and 2005. So day there are a lot of green parties all over the world, but and the German greens are the most successful, they are an example for other green parties.